Penerapan Metode Additive Ratio Assement (ARAS) dalam Pemilihan Customer Service Terbaik - Sri Agustiani Br Siburian; Mohammad Taufan Asri Zaen; Setiawansyah; Dodi Siregar; Erlin Windia Ambarsari; Yuwan Jumaryadi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
There are several references or assessments in determining the best customer service, including those based on customer service performance assessments, namely Cross Selling, Greeting Service Recovery, Grooming, and Discipline. In this study the authors used the ARAS method in selecting the best Customer Service. Use the Additive Ratio Assessment (ARAS) method where each criterion is compared to produce the best. The results of the study provide alternative A3 which is the alternative chosen to be the best alternative with a value of 0.2207.